Transport and interface characteristics of Te-doped NASICON solid electrolyte Li1.3Al0.3Ti1.7(PO4)3. (10th December 2021) - Wang, Qiaohui; Liu, Lei; Zhao, Bojie; Zhang, Lei; Xiao, Xiao; Yan, Hao; Xu, Guoli; Ma, Lei; Liu, Yong
Abstract: Te-doped NASICON-type Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP) electrolyte materials were prepared by ball milling-assisted solid state method. The structural, morphological, and transport properties of samples were analyzed through X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscope, energy dispersive X-Ray spectroscopy, electrochemical impedance spectroscopy, and DC polarization to determine optimal doping concentration. High total ionic conductivity of 7.03 × 10 −4 S cm −1 and negligible electronic conductivity of 7.64 × 10 −9 S cm −1 were obtained at room temperature for Li1.3 Al0.3 Te0.03 Ti1.67 (PO4 )3 electrolyte. Interface characteristics analysis of electrolyte materials with Li electrode showed that voltage profile of Li/Li1.3 Al0.3 Te0.03 Ti1.67 (PO4 )3 /Li cell remained stable after 300 h of cycling with current density of 0.02 mA cm −2 . Good cyclic stability at different temperatures was also demonstrated, with doped electrolyte presenting better interface stability than pure LATP. These results suggest that Te-doped LATP materials can be used as alternative solid electrolyte for all solid-state lithium-ion batteries.